Pengaruh Pengendalian Internal, Moralitas Individu, Komitmen Organisasi Dan Budaya Organisasi Terhadap Kecenderungan Kecurangan Akuntansi - Tyas Enggarin, Suryo; Maharani, Betari; Anissa Hakim, Purwantini (ACE: Accounting Research Journal, 2023)
ABSTRACT The tendency for accounting fraud often occurs in an organization. Many factors cause this fraud. This research will discuss several factors that often influence a person’s behavior towards accounting fraud tendencies. Therefore, this research aims to empirically test and analyze the factors that influence the tendency of accounting fraud namely internal control, individual morality, organizational commitment and organizational culture. The research population was 25 Regional Apparatus Organizations Kota Magelang and 10 Regional Apparatus Organizations Kabupaten Magelang. Questionnaire was used as a sampling technique in this quantitative research. The hypothesis test was done by using multiple linear regression analysis. The research result shows that internal control and Organizational Culture influence the tendency of accounting fraud, meanwhile organizational commitment and Individual Morality have no effect on the tendency of accounting fraud. Keywords: Internal Control; Individual Morality; Organizational Commitment; Organizational Culture; Tendency of Accounting Fraud ABSTRAK Penelitian ini bertujuan untuk menguji secara empiris dan menganalisis pengaruh pengendalian internal, moralitas individu, komitmen organisasi dan budaya organisasi terhadap kecenderungan kecurangan akuntansi. Populasi penelitian adalah seluruh Organisasi Perangkat Daerah (OPD) Kota Magelang dan Kabupaten Magelang yaitu 25 OPD Kota Magelang dan 10 OPD Kabupaten Magelang. Uji hipotesis dilakukan dengan menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa pengendalian internal dan budaya organisasi berpengaruh terhadap kecenderungan kecurangan akuntansi, sedangkan moralitas individu dan komitmen organisasi tidak berpengaruh terhadap kecenderungan kecurangan akuntansi.. Kata kunci: Pengendalian Internal; Moralitas Individu; Komitmen Organisasi; Budaya Organisasi; Kecenderungan Kecurangan Akuntansi